Gas-solid interface friction nanogenerator and preparation method and application thereof
Patent Information
- Application Number
- CN202211502176.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-28
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2042-11-28
AI Technical Summary
目前,关于淡水资源收集的研究大都基于水的蒸腾作用,利用光热转换器件将光转换为热,促进海水的蒸腾,实现海水淡化,在此过程中,由于水的蒸腾作用使水分子向上运动,存在巨大的机械能,然而该机械能却从未被利用
[0022]与现有技术相比,本发明提供了一种气-固界面摩擦纳米发电机及其制备方法和应用。本发明提供的气-固界面摩擦纳米发电机包括依次接触的吸水层、光热层和起电层;所述吸水层的成分包括水凝胶;所述光热层的成分包括光热转换材料和水凝胶;所述起电层的成分包括接触起电材料,所述接触起电材料与水接触和分离的过程中可产生电荷。在本发明中,所述吸水层具备良好的吸水能力,所述光热层具备吸水和促进水蒸发的作用,所述起电层可以将水蒸发向上运动的微小机械能转化为电能。本发明提供的气-固界面摩擦纳米发电机不仅可以将水蒸腾作用中的机械能转化为电能,还可以促进水的蒸发,实现海水淡化,在构建水电多重能源收集系统中具有良好的应用前景。
Smart Images

Figure CN115882747B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of triboelectric nanogenerator technology, and particularly relates to a gas-solid interface triboelectric nanogenerator, its preparation method and application. Background Technology
[0002] Triboelectric nanogenerators were first invented in 2012 by Academician Wang Zhonglin's team. Over the past decade, they have made significant progress. The principle of triboelectric nanogenerators is to convert minute mechanical energy in the environment into electrical energy through the coupling of contact electrification and electrostatic induction effects, providing a powerful supplement to existing energy sources. The contact interfaces of triboelectric nanogenerators include solid-solid, liquid-solid, gas-solid, and liquid-liquid interfaces, and this wide range of interfaces allows them to be applied in diverse environments.
[0003] Due to the uneven distribution and severe scarcity of freshwater resources on Earth, freshwater collection is of paramount importance. Currently, most research on freshwater collection is based on water transpiration, utilizing photothermal conversion devices to convert light into heat, promoting seawater transpiration and achieving desalination. During this process, water molecules move upwards due to transpiration, generating significant mechanical energy, which has never been utilized. Once utilized and converted into electrical energy, it would greatly supplement the current shortage of electrical energy. Summary of the Invention
[0004] In view of this, the purpose of this invention is to provide a gas-solid interface triboelectric nanogenerator, its preparation method and application. The triboelectric nanogenerator provided by this invention can not only convert the mechanical energy in water evaporation into electrical energy, but also promote water evaporation and realize seawater desalination.
[0005] This invention provides a gas-solid interface triboelectric nanogenerator, comprising a water-absorbing layer, a photothermal layer, and an electrifying layer in sequential contact;
[0006] The absorbent layer comprises hydrogel;
[0007] The photothermal layer comprises a photothermal conversion material and a hydrogel;
[0008] The electrifying layer comprises a contact electrifying material, which generates an electric charge during contact and separation from water.
[0009] Preferably, the hydrogels in the absorbent layer and the photothermal layer are independently selected from one or more of polyacrylamide-based hydrogels, polyvinyl alcohol-based hydrogels, polyoxyethylene hydrogels, and polyacrylic acid-based hydrogels.
[0010] Preferably, the content of photothermal conversion material in the photothermal layer is 0.1 to 0.5 wt%.
[0011] Preferably, both the photothermal conversion material and the contact electrification material are black conductive materials.
[0012] Preferably, the photothermal conversion material and the contact electrification material are independently selected from one or more of carbon black, single-walled carbon nanotubes, multi-walled carbon nanotubes, graphene, polypyrrole, Mxene, and carbon nanofiber yarn.
[0013] This invention provides a method for preparing the gas-solid interface triboelectric nanogenerator described above, comprising the following steps:
[0014] a) Mix the photothermal conversion material, the hydrogel precursor, and water to obtain a photothermal layer precursor dispersion; solidify the photothermal layer precursor dispersion to obtain a photothermal layer;
[0015] b) Mix the hydrogel precursor with water to obtain a water-absorbing layer precursor dispersion; solidify the water-absorbing layer precursor dispersion on one side of the photothermal layer to obtain a composite structure of the photothermal layer and the water-absorbing layer.
[0016] c) A contact electrifying material is coated onto the photothermal layer side of the composite structure to obtain a gas-solid interface triboelectric nanogenerator.
[0017] Preferably, in steps a) and b), the hydrogel precursor comprises a monomer, a crosslinking agent, a catalyst, and an initiator, or comprises a polymer and a crosslinking agent.
[0018] Preferably, the hydrogel precursor includes acrylamide, N,N'-methylenebisacrylamide, N,N,N'N'-tetramethylethylenediamine and ammonium persulfate, or includes polyvinyl alcohol and sodium tetraborate.
[0019] This invention provides a method for generating electricity, comprising the following steps:
[0020] The water-absorbing layer of the gas-solid interface triboelectric nanogenerator described in the above technical solution or the gas-solid interface triboelectric nanogenerator prepared by the above technical solution is placed in water; under light irradiation, water is transported from the water-absorbing layer to the photothermal layer and converted into water vapor in the photothermal layer; subsequently, the water vapor enters the charging layer due to evaporation and comes into contact with the charging material in the charging layer before separating to generate charge.
[0021] The present invention provides a seawater desalination device, including the gas-solid interface triboelectric nanogenerator described in the above technical solution or the gas-solid interface triboelectric nanogenerator prepared by the preparation method described in the above technical solution.
[0022] Compared with existing technologies, this invention provides a gas-solid interface triboelectric nanogenerator, its preparation method, and its applications. The gas-solid interface triboelectric nanogenerator provided by this invention comprises a water-absorbing layer, a photothermal layer, and a charging layer in sequential contact. The water-absorbing layer is composed of hydrogel; the photothermal layer is composed of a photothermal conversion material and hydrogel; the charging layer is composed of a contact charging material, which generates electric charge during contact and separation with water. In this invention, the water-absorbing layer has good water absorption capacity, the photothermal layer has the function of absorbing water and promoting water evaporation, and the charging layer can convert the minute mechanical energy of water evaporation upward movement into electrical energy. The gas-solid interface triboelectric nanogenerator provided by this invention can not only convert the mechanical energy of water evaporation into electrical energy, but also promote water evaporation, realizing seawater desalination, and has good application prospects in the construction of hydropower multi-energy harvesting systems. Attached Figure Description
[0023] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on the provided drawings without creative effort.
[0024] Figure 1 A schematic diagram of the structure of the gas-solid interface triboelectric nanogenerator provided by the present invention;
[0025] Figure 2 Comparison of water vapor evaporation rates of gas-solid interface triboelectric nanogenerators with different photothermal layer thicknesses provided by the present invention;
[0026] Figure 3 Comparison of water vapor evaporation rates of gas-solid interface triboelectric nanogenerators with different electrification layer thicknesses provided by the present invention.
[0027] Figure 4 A comparison diagram of triboelectric voltage of gas-solid interface triboelectric nanogenerators with different photothermal layer thicknesses provided by the present invention.
[0028] Figure 5 A comparison diagram of the triboelectric voltage of gas-solid interface triboelectric nanogenerators with different electrification layer thicknesses provided by the present invention. Detailed Implementation
[0029] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0030] This invention provides a gas-solid interface triboelectric nanogenerator, comprising a water-absorbing layer, a photothermal layer, and an electrifying layer in sequential contact;
[0031] The absorbent layer comprises hydrogel;
[0032] The photothermal layer comprises a photothermal conversion material and a hydrogel;
[0033] The electrifying layer comprises a contact electrifying material, which generates an electric charge during contact and separation from water.
[0034] In the gas-solid interface triboelectric nanogenerator provided by the present invention, the hydrogel in the water-absorbing layer includes, but is not limited to, one or more of polyacrylamide-based hydrogel, polyvinyl alcohol-based hydrogel, polyoxyethylene hydrogel, and polyacrylic acid-based hydrogel.
[0035] In the gas-solid interface triboelectric nanogenerator provided by the present invention, the water-absorbing layer is preferably formed by mixing a hydrogel precursor and water and then solidifying the mixture. The hydrogel precursor preferably includes a monomer, a crosslinking agent, a catalyst, and an initiator, or it may include a polymer and a crosslinking agent. In specific embodiments provided by the present invention, the hydrogel precursor preferably includes acrylamide, N,N'-methylenebisacrylamide, N,N,N'N'-tetramethylethylenediamine and ammonium persulfate, or includes polyvinyl alcohol and sodium tetraborate; the molar ratio of acrylamide, N,N'-methylenebisacrylamide, N,N,N'N'-tetramethylethylenediamine and ammonium persulfate is preferably 99.789:(0.01~0.05):(0.05~0.3):(0.01~0.05), specifically 99.789:0.028:0.152:0.031; the mass ratio of polyvinyl alcohol and sodium tetraborate is preferably 99.5:(0.1~1), specifically 99.5:0.5.
[0036] In the gas-solid interface triboelectric nanogenerator provided by the present invention, the thickness of the water-absorbing layer is preferably 3 to 5 cm, specifically 3 cm, 3.1 cm, 3.2 cm, 3.3 cm, 3.4 cm, 3.5 cm, 3.6 cm, 3.7 cm, 3.8 cm, 3.9 cm, 4 cm, 4.1 cm, 4.2 cm, 4.3 cm, 4.4 cm, 4.5 cm, 4.6 cm, 4.7 cm, 4.8 cm, 4.9 cm, or 5 cm.
[0037] In the gas-solid interface triboelectric nanogenerator provided by this invention, the photothermal conversion material in the photothermal layer is a black conductive material, including but not limited to one or more of carbon black, single-walled carbon nanotubes, multi-walled carbon nanotubes, graphene, polypyrrole, Mxene, and carbon nanofiber yarn; the diameter of the multi-walled carbon nanotubes is preferably 30-50 nm, and the length is preferably 0.5-2 μm; the content of the photothermal conversion material in the photothermal layer is preferably 0.1-0.5 wt%, specifically 0.1 wt%, 0.15 wt%, 0.2 wt%, 0.217 wt%, 0.25 wt%, 0.3 wt%, 0.35 wt%, 0.4 wt%, 0.45 wt%, or 0.5 wt%.
[0038] In the gas-solid interface triboelectric nanogenerator provided by the present invention, the hydrogel in the photothermal layer is preferably one or more of polyacrylamide-based hydrogel, polyvinyl alcohol-based hydrogel, polyoxyethylene hydrogel, and polyacrylic acid-based hydrogel.
[0039] In the gas-solid interface triboelectric nanogenerator provided by the present invention, the photothermal layer is preferably formed by mixing and solidifying a photothermal conversion material, a hydrogel precursor, and water. The composition and proportions of the hydrogel precursor have been described above and will not be repeated here.
[0040] In the gas-solid interface triboelectric nanogenerator provided by the present invention, the thickness of the photothermal layer is preferably 0.3 to 1.5 cm, specifically 0.3 cm, 0.4 cm, 0.5 cm, 0.6 cm, 0.7 cm, 0.8 cm, 0.9 cm, 1 cm, 1.1 cm, 1.2 cm, 1.3 cm, 1.4 cm or 1.5 cm.
[0041] In the gas-solid interface triboelectric nanogenerator provided by the present invention, the contact electrifying material in the electrifying layer is a black conductive material, including but not limited to one or more of carbon black, single-walled carbon nanotubes, multi-walled carbon nanotubes, graphene, polypyrrole, Mxene and carbon nanofiber yarn; the diameter of the multi-walled carbon nanotubes is preferably 30-50 nm, and the length is preferably 0.5-2 μm.
[0042] In the gas-solid interface triboelectric nanogenerator provided by the present invention, the deposition amount of the electrifying layer on the surface of the photothermal layer is preferably 0.5–5 mg / cm³. 2 Specifically, it can be 0.5 mg / cm³. 2 1mg / cm 2 1.5 mg / cm 2 2mg / cm 2 2.5 mg / cm 2 3mg / cm 23.5 mg / cm 2 4mg / cm 2 4.5 mg / cm 2 Or 5mg / cm 2 Alternatively, the thickness of the electrifying layer is preferably 1 to 10 μm, specifically 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm or 10 μm.
[0043] This invention also provides a method for preparing the gas-solid interface triboelectric nanogenerator described above, comprising the following steps:
[0044] a) Mix the photothermal conversion material, the hydrogel precursor, and water to obtain a photothermal layer precursor dispersion; solidify the photothermal layer precursor dispersion to obtain a photothermal layer;
[0045] b) Mix the hydrogel precursor with water to obtain a water-absorbing layer precursor dispersion; solidify the water-absorbing layer precursor dispersion on one side of the photothermal layer to obtain a composite structure of the photothermal layer and the water-absorbing layer.
[0046] c) A contact electrifying material is coated onto the photothermal layer side of the composite structure to obtain a gas-solid interface triboelectric nanogenerator.
[0047] In the preparation method provided by the present invention, the specific type of photothermal conversion material in step a) has been described above and will not be repeated here; the mass ratio of the photothermal conversion material to water is preferably (0.001~0.005):1, specifically 0.001:1, 0.0015:1, 0.002:1, 0.0025:1, 0.003:1, 0.0035:1, 0.004:1, 0.0045:1 or 0.005:1.
[0048] In the preparation method provided by the present invention, in step a), the composition and proportion of each component of the hydrogel precursor have been described above and will not be repeated here; the mass ratio of the hydrogel precursor to water based on the monomer mass is preferably 1:(1-5), specifically 1:1, 1:1.5, 1:2, 1:2.5, 1:3, 1:3.5, 1:4, 1:4.5 or 1:5; or, the mass ratio of the hydrogel precursor to water based on the polymer mass is preferably 1:(5-20), specifically 1:5, 1:6, 1:7, 1:8, 1:9, 1:10, 1:11, 1:12, 1:13, 1:14, 1:15, 1:16, 1:17, 1:18, 1:19 or 1:20.
[0049] In the preparation method provided by the present invention, in step a), the curing and molding is carried out in a mold; the curing and molding temperature is preferably 40-90℃, specifically 40℃, 45℃, 50℃, 55℃, 60℃, 65℃, 70℃, 75℃, 80℃, 85℃ or 90℃; the curing and molding time is not particularly limited, as long as the raw material is completely cured.
[0050] In the preparation method provided by the present invention, in step b), the composition and proportion of each component of the hydrogel precursor have been described above and will not be repeated here; the mass ratio of the hydrogel precursor to water based on the monomer mass is preferably 1:(1-5), specifically 1:1, 1:1.5, 1:2, 1:2.5, 1:3, 1:3.5, 1:4, 1:4.5 or 1:5; or, the mass ratio of the hydrogel precursor to water based on the polymer mass is preferably 1:(5-20), specifically 1:5, 1:6, 1:7, 1:8, 1:9, 1:10, 1:11, 1:12, 1:13, 1:14, 1:15, 1:16, 1:17, 1:18, 1:19 or 1:20.
[0051] In the preparation method provided by the present invention, in step b), the curing and molding is carried out in a mold with a built-in photothermal layer; the curing and molding temperature is preferably 40-90℃, specifically 40℃, 45℃, 50℃, 55℃, 60℃, 65℃, 70℃, 75℃, 80℃, 85℃ or 90℃; the curing and molding time is not particularly limited, as long as the raw material is completely cured.
[0052] The present invention also provides a method for generating electricity, comprising the following steps:
[0053] The water-absorbing layer of the gas-solid interface triboelectric nanogenerator described in the above technical solution or the gas-solid interface triboelectric nanogenerator prepared by the above technical solution is placed in water; under light irradiation, water is transported from the water-absorbing layer to the photothermal layer and converted into water vapor in the photothermal layer; subsequently, the water vapor enters the charging layer due to evaporation and comes into contact with the charging material in the charging layer before separating to generate charge.
[0054] The present invention also provides a seawater desalination device, including the gas-solid interface triboelectric nanogenerator described in the above technical solution or the gas-solid interface triboelectric nanogenerator prepared by the preparation method described in the above technical solution.
[0055] In the technical solution provided by this invention, the water-absorbing layer has good water absorption capacity, the photothermal layer has the function of absorbing water and promoting water evaporation, and the electrifying layer can convert the small mechanical energy of water evaporation upward movement into electrical energy. The technical solution provided by this invention can not only convert the mechanical energy of water evaporation into electrical energy, but also promote water evaporation to achieve seawater desalination, and has good application prospects in the construction of hydropower multi-energy harvesting systems.
[0056] For clarity, the following examples and comparative models will be used to provide a detailed description.
[0057] Example 1
[0058] S1) Mix multi-walled carbon nanotubes with water and disperse them uniformly in water to obtain an aqueous dispersion of multi-walled carbon nanotubes.
[0059] S2) The acrylamide-based hydrogel precursor (acrylamide, N,N'-methylenebisacrylamide, N,N,N'N'-tetramethylethylenediamine and ammonium persulfate) is dissolved in an aqueous dispersion of multi-walled carbon nanotubes to obtain a uniformly dispersed acrylamide-based hydrogel mixture of multi-walled carbon nanotubes. The mixture is then poured into a mold for curing at a curing temperature of 60°C to obtain a photothermal layer.
[0060] S3) The acrylamide-based hydrogel precursor (acrylamide, N,N'-methylenebisacrylamide, N,N,N'N'-tetramethylethylenediamine and ammonium persulfate) is dissolved in water to obtain an acrylamide-based hydrogel dispersion. Then, the acrylamide-based hydrogel dispersion is poured into a mold with a built-in photothermal layer for curing at a curing temperature of 60°C to obtain a composite structure of a photothermal layer and a water-absorbing layer.
[0061] S4) Multi-walled carbon nanotubes are deposited onto the photothermal layer side of the composite structure to obtain, as shown in the figure. Figure 1 The structure shown is a gas-solid interface triboelectric nanogenerator.
[0062] In this embodiment, in step S1), the multi-walled carbon nanotube has a diameter of 30-50 nm and a length of 0.5-2 μm; the mass ratio of the multi-walled carbon nanotube to water is 0.0025:1.
[0063] In steps S2) and S3), the contents of acrylamide, N,N'-methylenebisacrylamide, N,N,N'N'-tetramethylethylenediamine, and ammonium persulfate in the hydrogel precursor are 99.789 mol%, 0.028 mol%, 0.152 mol%, and 0.031 mol%, respectively; the mass ratio of acrylamide to water is 1:2.
[0064] In step S2), the mass percentage of multi-walled carbon nanotubes in the photothermal layer is 0.217%; the height of the photothermal layer is 0.5 cm.
[0065] In step S3), the height of the absorbent layer is 4 cm;
[0066] In step S4), the multi-walled carbon nanotubes used are the same as in S1); the deposition amount of the multi-walled carbon nanotubes is 1 mg / cm³. 2 .
[0067] Example 2
[0068] S1) Mix multi-walled carbon nanotubes with water and disperse them uniformly in water to obtain an aqueous dispersion of multi-walled carbon nanotubes.
[0069] S2) The acrylamide-based hydrogel precursor (acrylamide, N,N'-methylenebisacrylamide, N,N,N'N'-tetramethylethylenediamine and ammonium persulfate) is dissolved in an aqueous dispersion of multi-walled carbon nanotubes to obtain a uniformly dispersed acrylamide-based hydrogel mixture of multi-walled carbon nanotubes. The mixture is then poured into a mold for curing at a curing temperature of 60°C to obtain a photothermal layer.
[0070] S3) The acrylamide-based hydrogel precursor (acrylamide, N,N'-methylenebisacrylamide, N,N,N'N'-tetramethylethylenediamine and ammonium persulfate) is dissolved in water to obtain an acrylamide-based hydrogel dispersion. Then, the acrylamide-based hydrogel dispersion is poured into a mold with a built-in photothermal layer for curing at a curing temperature of 60°C to obtain a composite structure of a photothermal layer and a water-absorbing layer.
[0071] S4) Multi-walled carbon nanotubes are deposited onto the photothermal layer side of the composite structure to obtain, as shown in the figure. Figure 1 The structure shown is a gas-solid interface triboelectric nanogenerator.
[0072] In this embodiment, in step S1), the multi-walled carbon nanotube has a diameter of 30-50 nm and a length of 0.5-2 μm; the mass ratio of the multi-walled carbon nanotube to water is 0.0025:1.
[0073] In steps S2) and S3), the contents of acrylamide, N,N'-methylenebisacrylamide, N,N,N'N'-tetramethylethylenediamine, and ammonium persulfate in the hydrogel precursor are 99.789 mol%, 0.028 mol%, 0.152 mol%, and 0.031 mol%, respectively; the mass ratio of acrylamide to water is 1:2.
[0074] In step S2), the mass percentage of multi-walled carbon nanotubes in the photothermal layer is 0.217%; the height of the photothermal layer is 0.8 cm.
[0075] In step S3), the height of the absorbent layer is 3.7 cm;
[0076] In step S4), the multi-walled carbon nanotubes used are the same as in S1); the deposition amount of the multi-walled carbon nanotubes is 1 mg / cm³. 2 .
[0077] Example 3
[0078] S1) Mix multi-walled carbon nanotubes with water and disperse them uniformly in water to obtain an aqueous dispersion of multi-walled carbon nanotubes.
[0079] S2) The acrylamide-based hydrogel precursor (acrylamide, N,N'-methylenebisacrylamide, N,N,N'N'-tetramethylethylenediamine and ammonium persulfate) is dissolved in an aqueous dispersion of multi-walled carbon nanotubes to obtain a uniformly dispersed acrylamide-based hydrogel mixture of multi-walled carbon nanotubes. Then, it is poured into a mold for curing at a curing temperature of 60°C to obtain a photothermal layer.
[0080] S3) The acrylamide-based hydrogel precursor (acrylamide, N,N'-methylenebisacrylamide, N,N,N'N'-tetramethylethylenediamine and ammonium persulfate) is dissolved in water to obtain an acrylamide-based hydrogel dispersion. Then, the acrylamide-based hydrogel dispersion is poured into a mold with a built-in photothermal layer for curing at a curing temperature of 60°C to obtain a composite structure of a photothermal layer and a water-absorbing layer.
[0081] S4) Multi-walled carbon nanotubes are deposited onto the photothermal layer side of the composite structure to obtain, as shown in the figure. Figure 1 The structure shown is a gas-solid interface triboelectric nanogenerator.
[0082] In this embodiment, in step S1), the multi-walled carbon nanotube has a diameter of 30-50 nm and a length of 0.5-2 μm; the mass ratio of the multi-walled carbon nanotube to water is 0.0025:1.
[0083] In steps S2) and S3), the contents of acrylamide, N,N'-methylenebisacrylamide, N,N,N'N'-tetramethylethylenediamine, and ammonium persulfate in the hydrogel precursor are 99.789 mol%, 0.028 mol%, 0.152 mol%, and 0.031 mol%, respectively; the mass ratio of acrylamide to water is 1:2.
[0084] In step S2), the mass percentage of multi-walled carbon nanotubes in the photothermal layer is 0.217%; the height of the photothermal layer is 1 cm.
[0085] In step S3), the height of the absorbent layer is 3.7 cm;
[0086] In step S4), the multi-walled carbon nanotubes used are the same as in S1); the deposition amount of the multi-walled carbon nanotubes is 1 mg / cm³. 2 .
[0087] Example 4
[0088] S1) Mix multi-walled carbon nanotubes with water and disperse them uniformly in water to obtain an aqueous dispersion of multi-walled carbon nanotubes.
[0089] S2) The acrylamide-based hydrogel precursor (acrylamide, N,N'-methylenebisacrylamide, N,N,N'N'-tetramethylethylenediamine and ammonium persulfate) is dissolved in an aqueous dispersion of multi-walled carbon nanotubes to obtain a uniformly dispersed acrylamide-based hydrogel mixture of multi-walled carbon nanotubes. Then, it is poured into a mold for curing at a curing temperature of 60°C to obtain a photothermal layer.
[0090] S3) The acrylamide-based hydrogel precursor (acrylamide, N,N'-methylenebisacrylamide, N,N,N'N'-tetramethylethylenediamine and ammonium persulfate) is dissolved in water to obtain an acrylamide-based hydrogel dispersion. Then, the acrylamide-based hydrogel dispersion is poured into a mold with a built-in photothermal layer for curing at a curing temperature of 60°C to obtain a composite structure of a photothermal layer and a water-absorbing layer.
[0091] S4) Multi-walled carbon nanotubes are deposited onto the photothermal layer side of the composite structure to obtain, as shown in the figure. Figure 1 The structure shown is a gas-solid interface triboelectric nanogenerator.
[0092] In this embodiment, in step S1), the multi-walled carbon nanotube has a diameter of 30-50 nm and a length of 0.5-2 μm; the mass ratio of the multi-walled carbon nanotube to water is 0.0025:1.
[0093] In steps S2) and S3), the contents of acrylamide, N,N'-methylenebisacrylamide, N,N,N'N'-tetramethylethylenediamine, and ammonium persulfate in the hydrogel precursor are 99.789 mol%, 0.028 mol%, 0.152 mol%, and 0.031 mol%, respectively; the mass ratio of acrylamide to water is 1:2.
[0094] In step S2), the mass percentage of multi-walled carbon nanotubes in the photothermal layer is 0.217%; the height of the photothermal layer is 1.2 cm.
[0095] In step S3), the height of the absorbent layer is 3.3 cm;
[0096] In step S4), the multi-walled carbon nanotubes used are the same as in S1); the deposition amount of the multi-walled carbon nanotubes is 1 mg / cm³. 2 .
[0097] Example 5
[0098] S1) Mix multi-walled carbon nanotubes with water and disperse them uniformly in water to obtain a multi-walled carbon nanotube aqueous dispersion.
[0099] S2) The acrylamide-based hydrogel precursor (acrylamide, N,N'-methylenebisacrylamide, N,N,N'N'-tetramethylethylenediamine and ammonium persulfate) is dissolved in an aqueous dispersion of multi-walled carbon nanotubes to obtain a uniformly dispersed acrylamide-based hydrogel mixture of multi-walled carbon nanotubes. Then, it is poured into a mold for curing at a curing temperature of 60°C to obtain a photothermal layer.
[0100] S3) The acrylamide-based hydrogel precursor (acrylamide, N,N'-methylenebisacrylamide, N,N,N'N'-tetramethylethylenediamine and ammonium persulfate) is dissolved in water to obtain an acrylamide-based hydrogel dispersion. Then, the acrylamide-based hydrogel dispersion is poured into a mold with a built-in photothermal layer for curing at a curing temperature of 60°C to obtain a composite structure of a photothermal layer and a water-absorbing layer.
[0101] S4) Multi-walled carbon nanotubes are deposited onto the photothermal layer side of the composite structure to obtain, as shown in the figure. Figure 1 The structure shown is a gas-solid interface triboelectric nanogenerator.
[0102] In this embodiment, in step S1), the multi-walled carbon nanotube has a diameter of 30-50 nm and a length of 0.5-2 μm; the mass ratio of the multi-walled carbon nanotube to water is 0.0025:1.
[0103] In steps S2) and S3), the contents of acrylamide, N,N'-methylenebisacrylamide, N,N,N'N'-tetramethylethylenediamine, and ammonium persulfate in the hydrogel precursor are 99.789 mol%, 0.028 mol%, 0.152 mol%, and 0.031 mol%, respectively; the mass ratio of acrylamide to water is 1:2.
[0104] In step S2), the mass percentage of multi-walled carbon nanotubes in the photothermal layer is 0.217%; the height of the photothermal layer is 1.5 cm.
[0105] In step S3), the height of the absorbent layer is 3.7 cm;
[0106] In step S4), the multi-walled carbon nanotubes used are the same as in S1); the deposition amount of the multi-walled carbon nanotubes is 1 mg / cm³. 2 .
[0107] Example 6
[0108] S1) Mix multi-walled carbon nanotubes with water and disperse them uniformly in water to obtain an aqueous dispersion of multi-walled carbon nanotubes.
[0109] S2) The acrylamide-based hydrogel precursor (acrylamide, N,N'-methylenebisacrylamide, N,N,N'N'-tetramethylethylenediamine and ammonium persulfate) is dissolved in an aqueous dispersion of multi-walled carbon nanotubes to obtain a uniformly dispersed acrylamide-based hydrogel mixture of multi-walled carbon nanotubes. The mixture is then poured into a mold for curing at a curing temperature of 60°C to obtain a photothermal layer.
[0110] S3) The acrylamide-based hydrogel precursor (acrylamide, N,N'-methylenebisacrylamide, N,N,N'N'-tetramethylethylenediamine and ammonium persulfate) is dissolved in water to obtain an acrylamide-based hydrogel dispersion. Then, the acrylamide-based hydrogel dispersion is poured into a mold with a built-in photothermal layer for curing at a curing temperature of 60°C to obtain a composite structure of a photothermal layer and a water-absorbing layer.
[0111] S4) Multi-walled carbon nanotubes are deposited onto the photothermal layer side of the composite structure to obtain, as shown in the figure. Figure 1 The structure shown is a gas-solid interface triboelectric nanogenerator.
[0112] In this embodiment, in step S1), the multi-walled carbon nanotube has a diameter of 30-50 nm and a length of 0.5-2 μm; the mass ratio of the multi-walled carbon nanotube to water is 0.0025:1.
[0113] In steps S2) and S3), the contents of acrylamide, N,N'-methylenebisacrylamide, N,N,N'N'-tetramethylethylenediamine, and ammonium persulfate in the hydrogel precursor are 99.789 mol%, 0.028 mol%, 0.152 mol%, and 0.031 mol%, respectively; the mass ratio of acrylamide to water is 1:2.
[0114] In step S2), the mass percentage of multi-walled carbon nanotubes in the photothermal layer is 0.217%; the height of the photothermal layer is 0.8 cm.
[0115] In step S3), the height of the absorbent layer is 3.7 cm;
[0116] In step S4), the multi-walled carbon nanotubes used are the same as in S1); the deposition amount of the multi-walled carbon nanotubes is 2 mg / cm³. 2 .
[0117] Example 7
[0118] S1) Mix multi-walled carbon nanotubes with water and disperse them uniformly in water to obtain an aqueous dispersion of multi-walled carbon nanotubes.
[0119] S2) The acrylamide-based hydrogel precursor (acrylamide, N,N'-methylenebisacrylamide, N,N,N'N'-tetramethylethylenediamine, ammonium persulfate) is dissolved in an aqueous dispersion of multi-walled carbon nanotubes to obtain a uniformly dispersed acrylamide-based hydrogel mixture, which is then poured into a mold for curing at 60°C to obtain a photothermal layer.
[0120] S3) The acrylamide-based hydrogel precursor (acrylamide, N,N'-methylenebisacrylamide, N,N,N'N'-tetramethylethylenediamine and ammonium persulfate) is dissolved in water to obtain an acrylamide-based hydrogel dispersion. Then, the acrylamide-based hydrogel dispersion is poured into a mold with a built-in photothermal layer for curing at a curing temperature of 60°C to obtain a composite structure of a photothermal layer and a water-absorbing layer.
[0121] S4) Multi-walled carbon nanotubes are deposited onto the photothermal layer side of the composite structure to obtain, as shown in the figure. Figure 1 The structure shown is a gas-solid interface triboelectric nanogenerator.
[0122] In this embodiment, in step S1), the multi-walled carbon nanotube has a diameter of 30-50 nm and a length of 0.5-2 μm; the mass ratio of the multi-walled carbon nanotube to water is 0.0025:1.
[0123] In steps S2) and S3), the contents of acrylamide, N,N'-methylenebisacrylamide, N,N,N'N'-tetramethylethylenediamine, and ammonium persulfate in the hydrogel precursor are 99.789 mol%, 0.028 mol%, 0.152 mol%, and 0.031 mol%, respectively; the mass ratio of acrylamide to water is 1:2.
[0124] In step S2), the mass percentage of multi-walled carbon nanotubes in the photothermal layer is 0.217%; the height of the photothermal layer is 0.8 cm.
[0125] In step S3), the height of the absorbent layer is 3.7 cm;
[0126] In step S4), the multi-walled carbon nanotubes used are the same as in S1); the deposition amount of the multi-walled carbon nanotubes is 3 mg / cm³. 2 .
[0127] Example 8
[0128] S1) Mix multi-walled carbon nanotubes with water and disperse them uniformly in water to obtain a multi-walled carbon nanotube aqueous dispersion.
[0129] S2) The acrylamide-based hydrogel precursor (acrylamide, N,N'-methylenebisacrylamide, N,N,N'N'-tetramethylethylenediamine and ammonium persulfate) is dissolved in an aqueous dispersion of multi-walled carbon nanotubes to obtain a uniformly dispersed acrylamide-based hydrogel mixture of multi-walled carbon nanotubes. Then, it is poured into a mold for curing at a curing temperature of 60°C to obtain a photothermal layer.
[0130] S3) The acrylamide-based hydrogel precursor (acrylamide, N,N'-methylenebisacrylamide, N,N,N'N'-tetramethylethylenediamine and ammonium persulfate) is dissolved in water to obtain an acrylamide-based hydrogel dispersion. Then, the acrylamide-based hydrogel dispersion is poured into a mold with a built-in photothermal layer for curing at a curing temperature of 60°C to obtain a composite structure of a photothermal layer and a water-absorbing layer.
[0131] S4) Carbon nanotube fiber yarn is cut to the same area as the composite structure and laid flat on the photothermal layer side of the composite structure to act as a charging layer. The carbon nanotube fiber yarn is tightly bonded to the composite structure, resulting in... Figure 1 The structure shown is a gas-solid interface triboelectric nanogenerator.
[0132] In this embodiment, in step S1), the multi-walled carbon nanotube has a diameter of 30-50 nm and a length of 0.5-2 μm; the mass ratio of the multi-walled carbon nanotube to water is 0.0025:1.
[0133] In steps S2) and S3), the contents of acrylamide, N,N'-methylenebisacrylamide, N,N,N'N'-tetramethylethylenediamine, and ammonium persulfate in the hydrogel precursor are 99.789 mol%, 0.028 mol%, 0.152 mol%, and 0.031 mol%, respectively; the mass ratio of acrylamide to water is 1:2.
[0134] In step S2), the mass percentage of multi-walled carbon nanotubes in the photothermal layer is 0.217%; the height of the photothermal layer is 0.8 cm.
[0135] In step S3), the height of the absorbent layer is 3.7 cm;
[0136] In step S4), the carbon nanotube fiber yarn is manufactured by Shenzhen Xiwan Technology Co., Ltd., batch number: 2021-YM-4; the covering thickness of the carbon nanotube fiber yarn is 5μm.
[0137] Comparative Example 1
[0138] S1) Mix multi-walled carbon nanotubes with water and disperse them uniformly in water to obtain a multi-walled carbon nanotube aqueous dispersion.
[0139] S2) The acrylamide-based hydrogel precursor (acrylamide, N,N'-methylenebisacrylamide, N,N,N'N'-tetramethylethylenediamine and ammonium persulfate) is dissolved in a multi-walled carbon nanotube aqueous dispersion to obtain a uniformly dispersed acrylamide-based hydrogel mixture of multi-walled carbon nanotubes. Then, it is poured into a mold for curing at a curing temperature of 60°C to obtain a photothermal layer.
[0140] S3) The acrylamide-based hydrogel precursor (acrylamide, N,N'-methylenebisacrylamide, N,N,N'N'-tetramethylethylenediamine and ammonium persulfate) is dissolved in water to obtain an acrylamide-based hydrogel dispersion. Then, the acrylamide-based hydrogel dispersion is poured into a mold with a built-in photothermal layer for curing at a curing temperature of 60°C to obtain a composite structure of a photothermal layer and a water-absorbing layer.
[0141] In this comparative example, in step S1), the multi-walled carbon nanotubes have a diameter of 30–50 nm and a length of 0.5–2 μm; the mass ratio of the multi-walled carbon nanotubes to water is 0.0025:1.
[0142] In steps S2) and S3), the contents of acrylamide, N,N'-methylenebisacrylamide, N,N,N'N'-tetramethylethylenediamine, and ammonium persulfate in the hydrogel precursor are 99.789 mol%, 0.028 mol%, 0.152 mol%, and 0.031 mol%, respectively; the mass ratio of acrylamide to water is 1:2.
[0143] In step S2), the mass percentage of multi-walled carbon nanotubes in the photothermal layer is 0.217%; the height of the photothermal layer is 0.8 cm.
[0144] In step S3), the height of the absorbent layer is 3.3 cm.
[0145] Comparative Example 2
[0146] S1) Dissolve the acrylamide-based hydrogel precursor (acrylamide, N,N'-methylenebisacrylamide, N,N,N'N'-tetramethylethylenediamine and ammonium persulfate) in water to obtain an acrylamide-based hydrogel mixture, then pour it into a mold for curing at a curing temperature of 60°C to obtain an acrylamide-based hydrogel.
[0147] S2) Multi-walled carbon nanotubes are deposited onto the surface of an acrylamide-based hydrogel.
[0148] In this comparative example, in step S2), the multi-walled carbon nanotubes have a diameter of 30–50 nm and a length of 0.5–2 μm; the mass ratio of the multi-walled carbon nanotubes to water is 0.0025:1.
[0149] In step S1), the contents of acrylamide, N,N'-methylenebisacrylamide, N,N,N'N'-tetramethylethylenediamine, and ammonium persulfate in the hydrogel precursor are 99.789 mol%, 0.028 mol%, 0.152 mol%, and 0.031 mol%, respectively; the mass ratio of acrylamide to water is 1:2.
[0150] In step S2), the height of the acrylamide-based hydrogel is 4.5 cm;
[0151] In step S3), the deposition amount of the multi-walled carbon nanotubes is 1 mg / cm³. 2 .
[0152] Performance testing
[0153] The products obtained in Examples 1-8 and Comparative Examples 1-2 were tested, specifically including: measuring and analyzing the evaporation rate using a xenon lamp, and measuring and analyzing the open-circuit voltage using a Keithley 6514 electrometer.
[0154] Measurement and analysis results as follows Figures 2-4 As shown; where, Figure 2 To adjust the effect of the photothermal layer thickness on the water vapor evaporation rate, Figure 3 To adjust the effect of the electrodeposition layer thickness on the water vapor evaporation rate, Figure 4 To adjust the effect of the photothermal layer thickness on the triboelectric voltage, Figure 5 To adjust the effect of the thickness of the electrified layer on the triboelectric voltage. Figure 2 and Figure 4 In the example, CNT-0cm corresponds to Example 2, CNT-0.5cm corresponds to Example 1, CNT-0.8cm corresponds to Example 2, CNT-1.0cm corresponds to Example 3, CNT-1.2cm corresponds to Example 4, and CNT-1.5cm corresponds to Example 5. Figure 3 and Figure 5 In the middle, CNT-0 mg / cm 2 Response ratio 1, CNT-1mg / cm 2 Corresponding to Example 2, CNT-2mg / cm 2 Corresponding to Example 6, CNT-3mg / cm 2 Corresponding to Example 7, CNT-5μm corresponds to Example 8.
[0155] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A gas-solid interfacial triboelectric nanogenerator, characterized in that, It includes the absorbent layer, the photothermal layer, and the electrostatic layer that come into contact in sequence; The absorbent layer comprises hydrogel; The photothermal layer comprises a photothermal conversion material and a hydrogel; The electrifying layer comprises a contact electrifying material, which generates an electric charge during contact and separation from water. The photothermal conversion material and the contact electrification material are independently selected from one or more of carbon black, single-walled carbon nanotubes, multi-walled carbon nanotubes, graphene, polypyrrole, Mxene, and carbon nanofiber yarn; Under illumination, water is transported from the water-absorbing layer to the photothermal layer in the gas-solid interface triboelectric nanogenerator, where it is converted into water vapor. Subsequently, the water vapor enters the charging layer due to evaporation and comes into contact with the charging material in the charging layer before separating to generate an electric charge.
2. The gas-solid interface triboelectric nanogenerator according to claim 1, characterized in that, The hydrogels in the absorbent layer and the photothermal layer are independently selected from one or more of polyacrylamide-based hydrogels, polyvinyl alcohol-based hydrogels, polyoxyethylene hydrogels, and polyacrylic acid-based hydrogels.
3. The gas-solid interface triboelectric nanogenerator according to claim 1, characterized in that, The content of photothermal conversion material in the photothermal layer is 0.1~0.5wt%.
4. The gas-solid interface triboelectric nanogenerator according to claim 1, characterized in that, Both the photothermal conversion material and the contact electrification material are black conductive materials.
5. A method for preparing a gas-solid interface triboelectric nanogenerator according to any one of claims 1 to 4, characterized in that, Includes the following steps: a) Mix the photothermal conversion material, the hydrogel precursor, and water to obtain a photothermal layer precursor dispersion; solidify the photothermal layer precursor dispersion to obtain a photothermal layer; b) Mix the hydrogel precursor with water to obtain a water-absorbing layer precursor dispersion; solidify the water-absorbing layer precursor dispersion on one side of the photothermal layer to obtain a composite structure of the photothermal layer and the water-absorbing layer. c) A contact electrifying material is coated onto the photothermal layer side of the composite structure to obtain a gas-solid interface triboelectric nanogenerator.
6. The preparation method according to claim 5, characterized in that, In steps a) and b), the hydrogel precursor includes monomers, crosslinking agents, catalysts and initiators, or includes polymers and crosslinking agents.
7. The preparation method according to claim 5, characterized in that, The hydrogel precursor includes acrylamide, N,N'-methylenebisacrylamide, N,N,N',N'-tetramethylethylenediamine and ammonium persulfate, or includes polyvinyl alcohol and sodium tetraborate.
8. A seawater desalination device, characterized in that, This includes the gas-solid interface triboelectric nanogenerator as described in any one of claims 1 to 4, or the gas-solid interface triboelectric nanogenerator prepared by the preparation method described in any one of claims 5 to 7.
Citation Information
Patent Citations
Tree-like photo-thermal hydrogel as well as preparation method and application thereof
CN111218025A
